The illusion of the perfect alibi: Establishing the base rate of non‐offenders' alibis. Issue 1 (24th October 2016) - Nieuwkamp, Ricardo; Horselenberg, Robert; Van Koppen, Peter J.
Abstract: The present study was designed to establish the base rate of alibis and supportive evidence for alibis of non‐offenders. That is important because the presence and lack of an alibi are often seen as a clear indicator of innocence and guilt, respectively, of a suspect. A large sample of laypersons ( N = 841) was randomly assigned to one of 32 conditions in which they were asked to generate a true alibi after they were falsely accused of being the perpetrator of a mock robbery. Each condition consisted of either a Tuesday or a Saturday and one of 16 timeframes. In general, the majority of the participants had an alibi (99.5%) and supportive evidence for their alibis (92.4%). The supportive evidence often consisted of a combination of supportive evidence rather than one distinct form of supportive evidence (33.3%). Although it is widely assumed that the alibi believability is determined based on the strength of the supportive evidence, our results show that the type of evidence that can be presented by laypeople depends upon the day and the timeframe wherein the crime has been committed. The results of the study therefore imply that determining alibi believability solely on the strength of the supportive evidence is not a fair measure. We suggest that the believability should also be based on the base rate of alibis and its supportive evidence.